2018
DOI: 10.1002/jcb.27370
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐224 inhibition prevents progression of cervical carcinoma by targeting PTX3

Abstract: Cervical carcinoma is known as one of the most lethal and common conditions in women worldwide. Increasing evidence shows that microRNAs (miRs) may be involved in the pathogenesis of cervical carcinoma. This study investigates the correlation between expression of miR-224 in peripheral blood mononuclear cells and both diagnosis and prognosis of cervical carcinoma to clarify the effect miR-224 has on the biological behaviors of the subjected cervical carcinoma cells. Initially, 132 patients diagnosed with cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
(116 reference statements)
0
12
0
Order By: Relevance
“…miRNAs either degrade certain specific genes or inhibit their expression by binding to 3'-untranslated regions (3'-UTRs) of their mRNAs in a complimentary manner (5,6). miRNAs are widely involved in various biological processes including proliferation, tumor metastasis and drug tolerance (7,8). miR-34c-5p has been reported to function as a tumor suppressor in numerous cancer types (9).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs either degrade certain specific genes or inhibit their expression by binding to 3'-untranslated regions (3'-UTRs) of their mRNAs in a complimentary manner (5,6). miRNAs are widely involved in various biological processes including proliferation, tumor metastasis and drug tolerance (7,8). miR-34c-5p has been reported to function as a tumor suppressor in numerous cancer types (9).…”
Section: Introductionmentioning
confidence: 99%
“…The aberrant expression of hsa-miR-224-5p (miR-224) has been found to differ in distinct tumor tissues in comparison to adjacent normal tissues. It has been reported that miR-224 was upregulated in pancreatic cancer (Zhu et al 2018), renal cell carcinoma (Pan et al 2018), cervical 1 3 485 Page 2 of 10 carcinoma (Yu et al 2018), hepatocellular carcinoma (Hung et al 2018), and bladder cancer (Miao et al 2018), but low expression of miR-224 has been reported in prostate cancer (Gan et al 2018) and oral squamous cell carcinoma (Lu et al 2019). miR-224 seems to function differently in different cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a number of miRNAs are abnormally expressed during the occurrence and progression of cervical cancer (8). For example, miR-143 (9), miR-152 (10) and miR-506 (11) were downregulated in cervical cancer, whereas miR-21 (12), miR-224 (13) and miR-1297 (14) were expressed at high levels. Recent evidence has indicated that deregulated miRNAs may serve crucial roles in cervical cancer initiation and progression by regulating a wide range of biological functions (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%